Center for Applied Linguistics, Washington DC, USA. (13th March 2015) - Sugarman, Julie; Fee, Molly; Donovan, Anne
<x content-type="archive" xml:space="preserve">Abstract</x> The Center for Applied Linguistics (CAL) is a private, nonprofit organization with over 50 years' experience in the application of research on language and culture to educational and societal concerns. CAL carries out its mission to improve communication through better understanding of language and culture by engaging in a variety of projects in the areas of primary, secondary, and adult education, including research on effective strategies for the instruction of linguistically and ethnically diverse students; evaluation of the effectiveness of educational programs for such students; professional development for teachers and other staff working with linguistically diverse students; development of instructional materials and language tests; and services to support cultural orientation of immigrants and refugees.